Thanatophoric dysplasia, an enigmatic dilemma: a case report - Rai, Chanda; Gaikwad, Harsha Shailesh; Gaikwad, Harsha Shailesh; Bajaj, Sunil Kumar; Bajaj, Sunil Kumar; Gupta, Rohini; Gupta, Rohini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Thanatophoric dysplasia is a rare, fatal form of skeletal dysplasia that affects fetus in utero. It is characterized by marked underdevelopment of fetal skeleton and short limbs. This disorder can be diagnosed antenatally and the couple should be counselled for termination of pregnancy. 20 years old female came in her second trimester carrying an ultrasound report which showed features of thanatophoric dwarfism. She was advised to terminate her pregnancy but she decided to continue with her pregnancy. She was induced after 40 weeks and she delivered a stillborn baby with dwarf like features, a condition identified as thanatophoric dwarfism. Early diagnosis can be done by ultrasound as early as 13 weeks of gestation and since babies born with thanatophoric dysplasia have a very poor prognosis, couples should be counselled regarding early termination of pregnancy. 3D ultrasound scan and molecular analysis can also help identify this disorder.